ANALISIS IMPLEMENTASI PELAPORAN BARANG MILIK DAERAH DI KABUPATEN DONGGALA - Ranusentika, Dwi Sapto (Katalogis, 2016)
This research is aimed to seek and analyze: 1) the implementation of regional’s assets reporting in Donggala Regency; 2) factors that impede the implementation of regional assets reporting in Donggala Regency. Type of the research is descriptive qualitative and its population consists of 58 governmental instution units that manage the regional assets in Donggala Regency. The research applies census-sampling technique by whuich all population selected as respondents. The results show that : 1) the implementation of regional’s assets reporting in Donggala Regency from various dimensions such as communications, resource, and bureaucraticstructure has not been implemantend properly, but disposition; 2) factors the impede the implementation of regional assets reporting in Donggala regency include low-skilled human resources in using SIMDA BMD and lack of standardized administrative supporting facilities such as computers that can contribute to reporting system inefficiency.